Surveillance on the coverage of herpes zoster vaccine and post-marketing adverse events in Jiangsu province, China - Xiang Sun; Lei Zhang; Tingting Zhang; Jinning Sun; Yan Xu; Li Liu; Yuan Bao Liu; Ran Hu; YaLi Fu; Zhiguo Wang; Hui Sun (Human Vaccines & Immunotherapeutics, 2025)
To analyze the coverage rate of adult herpes zoster (HZ) vaccine and the incidence of Adverse event following immunization (AEFI) in Jiangsu province, China. The vaccination information of HZ vaccine in people aged 50 years and above in Jiangsu province in 2023 and the AEFI information of HZ vaccine from 2020 to 2023 were collected through the Jiangsu Province vaccination management information system and China AEFI information management system, and the vaccination rate and AEFI incidence of HZ vaccine were analyzed. The overall vaccination rate among individuals aged 50 years and above was merely 0.19%. About 20% of vaccinated individuals (12,821 people) received only the first dose, failing to complete the recommended two-dose regimen. A total of 43 and 217 cases of AEFIs following vaccination were reported after administration of the HZ vaccine during the periods of 2020–2021 and 2022–2023, respectively, resulting in reporting rates (RRs) of 240.7 and 201.2 per 100,000 doses, correspondingly. The majority of AEFIs following vaccination with HZ vaccines were common reactions, while rare reactions and coincidental events accounted for only 1.5% and 0.4% of cases, respectively. Over 55% of AEFIs occurred within 30 minutes post-vaccination , with fever, allergic eruptions, and drowsiness being the most reported systemic symptoms, and redness and induration being the main symptoms at the injection site. Despite the proven safety profile of the HZ vaccine, its coverage remains significantly low among individuals aged 50 years and above in Jiangsu Province, China as of 2023. The majority of AEFIs were mild and commonly observed. To enhance the comprehensiveness of post-marketing safety data, it is imperative to conduct further active surveillance studies.